PERSEPSI GENERASI Z TERHADAP PENGHITUNGAN WETON DALAM PERNIKAHAN ADAT JAWA DI KECAMATAN CIMANGGU, CILACAP, JAWA TENGAH - Wiyasri, Megi; Martono, Nanang; Dasuki, Niken Paramarti (SOSIOLOGI: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2025)
The tradition of calculating weton in Javanese customary marriages remains a cultural practice that endures amid modernization. This study aims to describe the perceptions of generation Z in Gumilang Village regarding the tradition of calculating weton in Javanese customary marriages. This research uses a qualitative method. Data were collected through observation, interviews, and documentation. The sampling technique employed purposive sampling. Data analysis was conducted using an interactive analysis method, which includes stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that informants who trust in weton calculation are motivated by obedience to their parents and respect for customary traditions. Conversely, informants who choose not to believe in weton calculation consider it irrational and unrelated to their marital destiny. These findings indicate that the beliefs of generation Z today represent their compliance with parental authority, rather than being based on consciously held individual beliefs. Theoretically, these findings affirm that power (authority) serves as a strategy to preserve beliefs that have been passed down through generations.